American Thoracic Society 2018 pediatric core curriculum. Issue 1 (28th November 2018) - Moore, Paul E.; Boyer, Debra; Thomas, Caroline S.; Brown, Rebekah F.; Cogen, Jonathan; Ong, Thida; Puranik, Sandeep; Peterson‐Carmichael, Stacey; Bishay, Lara; Rosen, Rachel; Cheng, Pi C. (Jennifer); Mayer, Oscar H.; et al.
Abstract: The American Thoracic Society Pediatric Core Curriculum updates clinicians annually in pediatric pulmonary disease in a 3‐4 year recurring cycle of topics. The 2018 course was presented in May during the annual International Conference.